GaN-HEMT dynamic ON-state resistance characterisation and modelling - Li, Ke; Evans, Paul; Johnson, Christopher Mark (2016)
GaN-HEMTs suffer from trapping effects which might increase device ON-state resistance (RDS(on)) values. Thus, dynamic RDS(on) of a commercial GaN-HEMT is characterized at different bias voltages in the paper by a proposed measurement circuit. Based on the measurement results, a behavioural model is proposed to represent device dynamic RDS(on) values, in which trapping and detrapping time constant is represented by a series of RC network. The model is simulated in PSPICE, of which the simulation results of RDS(on) values are compared and validated with the measurement when device switches in a power converter with different duty cycles and switching voltages. The results show that RDS(on) values of this device would increase due to trapping effects.